Genetic Engineering of Mesenchymal Stem Cells to Induce Their Migration and Survival - Janowski, Miroslaw; Lukomska, Barbara; Walczak, Piotr; Nowakowski, Adam (Stem cells international, 2016)
Mesenchymal stem cells (MSCs) are very attractive for regenerative medicine due to their relatively easy derivation and broad range of differentiation capabilities, either naturally or induced through cell engineering. However, efficient methods of delivery to diseased tissues and the long-term survival of grafted cells still need improvement. Here, we review genetic engineering approaches designed to enhance the migratory capacities of MSCs, as well as extend their survival after transplantation by the modulation of prosurvival approaches, including prevention of senescence and apoptosis. We highlight some of the latest examples that explore these pivotal points, which have great relevance in cell-based therapies.